1974
DOI: 10.1177/000348947408300109
|View full text |Cite
|
Sign up to set email alerts
|

Senile Changes in the Middle Ear Joints

Abstract: Histological study of the 1M and IS joints in 125 ears from 86 individuals varying in age from infancy to 96 years showed arthritic changes which increased in severity with advancing age. The earliest changes in the articular cartilage consisted of fraying and fibrillation, followed by thinning and calcification. The joint capsule showed atrophy and hyalinization and the articular disc showed hyaline deposits in early cases and calcium deposits in severe cases. Audiograms which were available on 55 ears showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
5
3

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 4 publications
2
37
5
3
Order By: Relevance
“…Willi (2003) describes a trend of a decrease of 457 sound transmission at higher frequencies (> 3 kHz) with age in fresh human temporal bones, 458 which would have to be confirmed in further measurements. Several morphological 459 parameters of the IMJ may change with age including hyalinization or calcification of the 460 joint capsule, thinning and calcification of the articular cartilage, thinning and calcification of 461 the disc, and arthritis resulting in narrowing or obliteration of the joint space (Gussen, 1971; 462 Etholm and Belal, 1974). In addition, the amount of elastic fibers in the joint capsule tends to 463 decrease with age (Harty, 1953), which may result in a reduction of the joint tension.…”
Section: Quantification Of the Imj Mobility 211mentioning
confidence: 99%
See 2 more Smart Citations
“…Willi (2003) describes a trend of a decrease of 457 sound transmission at higher frequencies (> 3 kHz) with age in fresh human temporal bones, 458 which would have to be confirmed in further measurements. Several morphological 459 parameters of the IMJ may change with age including hyalinization or calcification of the 460 joint capsule, thinning and calcification of the articular cartilage, thinning and calcification of 461 the disc, and arthritis resulting in narrowing or obliteration of the joint space (Gussen, 1971; 462 Etholm and Belal, 1974). In addition, the amount of elastic fibers in the joint capsule tends to 463 decrease with age (Harty, 1953), which may result in a reduction of the joint tension.…”
Section: Quantification Of the Imj Mobility 211mentioning
confidence: 99%
“…The IMJ connects the articular surfaces of the malleus and incus and has a twisted 41 saddle shape (Helmholtz 1863;Etholm and Belal, 1974;Sim and Puria, 2008). It has 42 previously been described in the literature as a synovial joint (diarthrodial joint/diarthrosis) 43 (Politzer, 1884;Harty, 1953Harty, , 1964Etholm and Belal, 1974;Schuknecht, 1974;Marquet, 44 1981; Hüttenbrink and Pfautsch, 1987;FICAT, 1998;Sim and Puria, 2008).…”
Section: Introduction 36mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the outer and middle ear associated with aging have been documented in the literature. These may include collapsing of the cartilaginous external auditory canal (Randolph and Schow 1983), stiffening of the tympanic membrane and ossicular chain (Etholm and Belal 1974;Ruah et al 1991). Hinojosa and Naunton (1980) summarized a number of tissue changes in the aging ear canal including a reduction of epithelial cell production, aging of extracellular substances (elastic tissue, cartilage, and bone), and extracellular deposition of various materials.…”
Section: Introductionmentioning
confidence: 99%
“…127 'Moderate' to 'severe' arthritic changes in the malleo-incudal joint were found in all 36 ears taken from individuals older than 70 years, and also in a significant proportion of younger ears, although the donors showed no clinical evidence of middle-ear disease. 126 If flexibility decreases acoustic transmission, joint fusion may increase the sound intensities to which the cochlea is exposed; it is interesting in this regard to note that elderly people are at increased risk of noise-induced hearing loss. 128 A histological study of rheumatoid arthritis has also suggested malleo-incudal and incudo-stapedial joint involvement, 129 and the expected increase in stiffness of the middle ear has been documented.…”
Section: Flexibility and Pressure-bufferingmentioning
confidence: 99%